A COMPARATIVE STUDY OF SURVIVAL, HOPE, AND THE LOVE OF LIFE ACROSS CULTURES (World Bulletin of Social Sciences, 2025)
The article analyzes thematic and lingua-poetic features of the stories “Love of Life” (Jack London) and “A Life Out of Thousands” (Abdulla Qahhor). Both protagonists in these stories confront the brink of death with unwavering resilience and an enduring love for life; Jack London portrayed a nameless traveler who struggled against the harsh Canadian tundra during the Gold Rush, emphasizing nature as an antagonistic force and survival as a primal instinct. Jack London and Abdulla Qahhor followed the principle of form and content when depicting the inner world of their protagonists.